Sedimentary Structures of the Jutana Dolomite and the Baghanwala Formation - Ghouri, Arif Ali Khan (Journal of Himalayan Earth Sciences, 1979)
The Jutana Dolomite and the Baghanwala Formation are well exposed in the Khewra Gorge, the type locality for the Cambrian sequence in the Salt Range. The Jutana Dolomite conformably overlies the Khussak Formation and is conformably overlain by the Baghanwala Formation. The two formations represent deposition during Early to Middle Cambrian and in fact form a part of a megacycle which started with the deposition of the Salt Range Formation under arid and well oxygenated environment and culminated with the deposition of the Baghanawala Formation which was also deposited under the same environments. In the two formations, several primary, secondary and organic structures are well preserved. In this paper the writer has described some of the most interesting and conspicuous primary, secondary and organic structures well preserved in the underlying Jutana Dolomite and the overlying Baghanwala Formation.